Do board characteristics matter in the relationship between intellectual capital efficiency and firm value? Evidence from the Nigerian oil and gas downstream sector - Ahmed Jinjiri Bala; Aminu Hassan; Muhammad Liman Muhammad (Future Business Journal)
Abstract Purpose The purpose of this study is to investigate the moderating effects of board characteristics such as board size, chief executive officer duality, number of board meetings, and diversity, on the relationship between intellectual capital efficiency and firm value in the Nigerian oil and gas downstream sector. Design/methodology/approach We collected time-series cross-sectional data from eight (8) downstream-sector oil and gas companies quoted on the Nigerian Exchange Group for the period 2004–2020. We analysed the data using Prais–Winsten regression with panel-corrected standard errors. Findings Overall, our results show no significant direct relationship between the modified value-added intellectual coefficient and our two measures of firm value (Tobin’s Q and Price Earnings Ratio (PER)). However, the board size is found to moderate the intellectual capital efficiency–PER relationship significantly and negatively, whereas board diversity significantly positively moderates the association between the modified value-added intellectual coefficient and PER. Our multi-theory framework, which blends clean surplus, agency, stakeholder, and resource-based theories is found to be relevant in underpinning this study. Research limitations/implications The research relies on 17-year panel data for eight downstream-sector oil and gas companies. Consequently, future research within intellectual capital efficiency in Nigeria could incorporate related sectors like midstream and upstream to enable comparability and expand generalization. Practical implication Policymakers may adopt the study findings to serve as a robust empirical base to demand improved board diversity as a catalyst for boosting the potency of the intellectual capital efficiency-firm value relationship. Originality/value Firstly, to the best of our knowledge, this study is the pioneer attempt to use board characteristics as moderators of the relationship between intellectual capital efficiency and firm value. Secondly, we develop and use a novel theoretical framework that combines clean surplus, agency, stakeholder, and resource-based theories to underpin the study.